AANZFTA – strefa wolnego handlu między ASEAN, Australią i Nową Zelandią - Żołądkiewicz, Krystyna (AANZFTA – ASEAN-Australia-New Zealand free trade area, 2009)
AANZFTA Agreement was signed in February 2009. Together, the 12 countries involved in the ASEAN FTA have a combined population of 600 million people and an estimated GDP exceeding US$ 2 700 billion. Beyond market access for goods and services, FTA will provide more opportunities and greater transparency for business people wishing to invest in the members markets. The importance of FTA is reflected in the high rate of growth in trade and its comprehensiveness. AANZFTA creates new opportunities for all members due to new ties within one of the world’s dynamic economic regions and one of the largest export markets
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 25-39